Monitoring of the Adult Patient on Venoarterial Extracorporeal Membrane Oxygenation - Mabel Chung; Ariel L. Shiloh; Anthony Carlese (The Scientific World Journal)
Venoarterial extracorporeal membrane oxygenation (VA ECMO) provides mechanical support to the patient with cardiac or cardiopulmonary failure. This paper reviews the physiology of VA ECMO including the determinants of ECMO flow and gas exchange. The efficacy of this therapy may be determined by assessing patient hemodynamics and device flow, overall gas exchange support, markers of adequate oxygen delivery, and pulsatility of the arterial blood pressure waveform.